Analog and pulse circuits - Lakshmaiah, Dayaydi; Ramarao, C. B.; Rao, K. Kishan (BS Publications, 2022)
This book is intended for anyone who has an interest to learn the analysis and design of analog and digital systems. The book covers the foundation of analysis and design of all analog and pulse circuits. The book is organized into seven chapters. In each chapter, practical derivations are explained step by step. Note: T& F does not sell or distribute the Hardback in India, Pakistan, Nepal, Bhutan, Bangladesh and Sri Lanka.